Efficacy and Safety of Anti–Nerve Growth Factor Antibody Therapy for Hip and Knee Osteoarthritis: A Meta-analysis. Issue 4 (25th April 2022) - Gao, Yijie; Hu, Zhengxu; Huang, Yi; Liu, Weijian; Ren, Changle
Background: The efficacy and safety of anti–nerve growth factor (NGF) antibody therapy used for osteoarthritis (OA) pain are controversial. Purpose: To evaluate the efficacy and safety of anti-NGF antibody therapy via a meta-analysis of randomized controlled trials (RCTs). Study Design: Systematic review; Level of evidence, 1. Methods: PubMed, the Cochrane Central Register of Controlled Trials, Embase, and the Web of Science databases were searched for RCTs assessing anti-NGF antibody treatments for hip and knee OA. A total of 623 records were retrieved from the databases. A random-effects model was used to assess primary and secondary outcomes. Bias was assessed using the Cochrane Collaboration tool, funnel plots, and the Egger test. Subgroup analyses were used to assess the efficacy and safety of the independent variables. Sensitivity analysis was conducted to evaluate the effectiveness of tanezumab and the effectiveness of anti-NGF antibodies compared to active comparator drugs. We present the effects of dose, administration mode, and treatment duration on the efficacy and safety of anti-NGF antibody therapy. Results: There were 19 RCTs included in our meta-analysis. Anti-NGF antibody treatment showed significant improvements on the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) for pain, physical function, and stiffness as well as on a patient global assessment (PGA). The overall standardized mean differences were as follows: WOMAC pain (–0.31 [95% CI, –0.36 to –0.26]; Z = 11.75; P < .001; I 2 = 38%), WOMAC physical function (−0.36 [95% CI, –0.41 to –0.30]; Z = 12.67; P < .001; I 2 = 44%), WOMAC stiffness (–3.59 [95% CI, –4.87 to –2.30]; Z = 5.47; P < .001; I 2 = 98%), and PGA (−0.28 [95% CI, –0.34 to –0.22]; Z = 9.39; P < .001; I 2 = 50%). Anti-NGF antibody treatment resulted in a greater incidence of adverse events (risk ratio, 1.09 [95% CI, 1.06 to 1.12]; Z = 5.60; P < .001; I 2 = 0%). The incidence of serious adverse events was similar between the treatment and control groups (risk ratio, 1.15 [95% CI, 0.98 to 1.34]; Z = 1.71; P = .09; I 2 = 0%). Conclusion: Anti-NGF antibody treatment significantly relieved pain and improved function in patients with hip and knee OA. However, no conclusion could be drawn regarding the optimal treatment plan for anti-NGF antibodies when all 3 variables (dose, administration mode, and treatment duration) were combined in the analyses.